2015
DOI: 10.1038/ncomms7766
|View full text |Cite
|
Sign up to set email alerts
|

Long distance spin communication in chemical vapour deposited graphene

Abstract: Graphene is an ideal medium for long-distance spin communication in future spintronic technologies. So far, the prospect is limited by the smaller sizes of exfoliated graphene flakes and lower spin transport properties of large-area chemical vapour-deposited (CVD) graphene. Here we demonstrate a high spintronic performance in CVD graphene on SiO2/Si substrate at room temperature. We show pure spin transport and precession over long channel lengths extending up to 16 μm with a spin lifetime of 1.2 ns and a spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
222
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(236 citation statements)
references
References 63 publications
13
222
0
1
Order By: Relevance
“…We find that EY relaxation is the dominant mechanism for spin relaxation at large µ, but DP spin relaxation becomes important at small µ since it is inversely proportional to the Drude relaxation time. This agrees with the experimental observations of spin relaxation in exfoliated graphene 49 and CVD graphene, 51 which indicate that both EY and DP spin relaxation mechanisms are present in graphene.…”
Section: Spin Relaxationsupporting
confidence: 81%
“…We find that EY relaxation is the dominant mechanism for spin relaxation at large µ, but DP spin relaxation becomes important at small µ since it is inversely proportional to the Drude relaxation time. This agrees with the experimental observations of spin relaxation in exfoliated graphene 49 and CVD graphene, 51 which indicate that both EY and DP spin relaxation mechanisms are present in graphene.…”
Section: Spin Relaxationsupporting
confidence: 81%
“…Magnetotransport measurements revealed that graphene in contact with WS 2 exhibits a large weak antilocalization (WAL) peak, revealing a strong SOC induced by proximity effects [24][25][26]30]. Fits to the magnetoconductance yielded spin lifetimes τ s ≈ 5 ps, which is two to three orders of magnitude lower than graphene on traditional substrates [10,31]. It was later asserted that after the removal of a temperatureindependent background, τ s becomes at most only a few hundred femtoseconds [26].…”
mentioning
confidence: 99%
“…5,6 The initial spin transport studies were mainly performed on single-layer [7][8][9][10] and bilayer exfoliated graphene, 9,11 and large-area graphene [12][13][14][15] deposited on conventional SiO 2 substrates. Although enhanced spin-relaxation times have been reported for bilayer graphene-based devices compared with those based on a single layer, the relatively low spin diffusion constants overall yield a lower spin-relaxation length of only 1-2 μm, 9,11 far below the theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%